THE EFFECT OF WORK LIFE QUALITY ON WORK MOTIVATION THROUGH JOB SATISFACTION AS A MEDIATION VARIABLE IN THE DEPARTMENT OF FOOD CROP, HORTICULTURE, PLANTATIONS AND FOOD SECURITY OF SIDRAP REGENCY - Agustan, Andi Ahmad Adhiim; Musa, Muhammad Ichwan; Dipoatmodjo, Tenri Sayu Puspitaningsih (Universitas Negeri Makassar, 2025)
Abstract: This study aims to measure the impact of Quality of Work Life on Work Motivation with Job Satisfaction as a Mediating variable at the Food Crops, Horticulture, Plantation and Food Security Service. This study uses a quantitative method with a descriptive approach. The population in this study were ASN of the Food Crops, Horticulture, Plantation and Food Security Service. Data were collected through questionnaires distributed to 41 employees as samples, the sampling method was the saturated sampling method and analyzed using the Structural Equation Modeling (SEM) analysis technique supported by Smart PLS 4.0 software. The data analysis process includes validity testing, reliability testing, and structural model testing. The results showed that the Quality of Work Life variable has a positive and significant effect on Work Motivation and Job Satisfaction. However, the effect of Job Satisfaction on Work Motivation is not statistically significant. In addition, Job Satisfaction is not able to significantly mediate the relationship between Quality of Work Life and Work Motivation.Keywords: Quality of Work Life, Work Motivation, Job Satisfaction